TERRORISM: REALITY AND FUTURE - Sergey Ivanovich Grachev; Anastasia Sergeevna Morozova (Современная наука и инновации, 2022)
The article analyzes the facts of terrorist acts (acts) for the current year. We consider the criminal activities of the international terrorist organization «Islamic State». There is a trend of criminal acts IG adherents in Russia, passed through the fighting in Syria.